A insubordinação criativa e o desenho universal pedagógico: reflexões sobre as práticas docentes dos professores que ensinam matemática nos anos iniciais - Sousa Neta, Felismina de (2024)
Commitment to an inclusive educational practice requires creative insubordination. To this end, teachers face difficulties when they feel unprepared to assist everyone in the teaching and learning process. The aim was to analyze evidence of Creative Insubordination (IC, abbreviation in Portuguese) in the inclusive practices of early years teachers, based on pedagogical actions, in the context of Universal Pedagogical Design (DUP, abbreviation in Portuguese), to improve mathematics teaching. This research took place in the context of the extension course, “Teacher training from the perspective of learning profiles: an experience with the Fedathi Sequence and Objectification Theory,” with three teachers, the subjects of the research. In order to achieve the general objective, we specifically sought to: (1) identify the aims of IC and DUP, with an emphasis on inclusive practices to improve mathematics teaching; (2) understand the training processes with an emphasis on IC and DUP, through inclusive practices aimed at mathematics teaching; and (3) verify the aspects of IC in inclusive teaching practices in mathematics teaching during a training action with early years teachers in the light of DUP. This research is based mainly on the studies of Borges Neto (2018), D’Ambrosio and Lopes (2015), Sousa (2017) and Sousa et al. (2013), on the conception of teaching. As a concept of learning, Vygotsky’s theories were used to complement the studies by Kranz (2015) and Lustosa and Figueiredo (2021). To discuss inclusion practices from a global perspective, we used the studies by Mantoan and Lanuti (2021, 2022). To discuss practices in the light of the DUP, the studies by Caetano (2018, 2019), Cardoso (2023), Kranz (2015) and Siqueira (2019) were analyzed. Methodologically, a qualitative, basic and exploratory approach was adopted. With a qualitative focus, the research was carried out in four stages: (1) state of the art, with a literature review; (2) collaborative study, to plan the didactic sessions; (3) case study, with the experience of the extension course; and (4) data analysis, with exploration of the semi-structured interview, adopting the content analysis method. It is considered that this research raises discussions that help towards a greater understanding of practices that enable the inclusion of all in the process of teaching and learning mathematics, as well as contributing to the emergence of new reflections on the different conceptions attributed to inclusion.